Transient Hyponatremia during Hospitalization for Acute Heart Failure - Verbrugge, Frederik H. (Am J Med, 2016)
OBJECTIVE: To study whether the temporal pattern of transient hyponatremia development in acute heart failure might provide insight into its pathophysiology and prognostic relevance. METHODS: A post-hoc analysis of the ESCAPE and DOSE AHF studies was performed (n=716). Patients were stratified according to the temporal pattern of hyponatremia development: (1) no hyponatremia; (2) persistent hyponatremia; (3) decompensation hyponatremia disappearing with decongestive treatment; and (4) treatment-induced hyponatremia. RESULTS: Transient decompensation versus no hyponatremia was associated with significantly elevated blood urea nitrogen/creatinine ratio (P-value<0.001), plasma renin activity (P-value<0.001), and plasma aldosterone levels (P-value<0.001) at baseline. Disease severity characteristics of such patients were intermediate between no and persistent hyponatremia. In contrast, patients with treatment-induced versus no hyponatremia had similar baseline characteristics, comparable natriuretic peptide levels, and both groups had little neurohumoral activation at baseline. Diuretic efficacy, defined as net fluid balance [mL] per 40 mg furosemide-equivalent dose administered, was lower in patients with persistent or treatment-induced hyponatremia versus decompensation hyponatremia or no hyponatremia, respectively. The former versus latter groups also had more pronounced neurohumoral activation with decongestive treatment. The risk for all-cause mortality [HR (95%CI) = 2.50 (1.50-4.19); P-value<0.001] and death or heart failure readmission [HR (95%CI) = 2.18 (1.60-2.97); P-value<0.001] was significantly elevated in patients with persistent versus no hyponatremia, with the risk of decompensation and treatment-hyponatremia situated in-between. CONCLUSIONS: Transient hyponatremia is prognostically relevant, but has a heterogeneous etiology according to its temporal pattern of development.